Efeito da aplicação foliar de silício no manejo, na produção e na qualidade dos frutos do meloeiro - Soares, Jordânia Medeiros (2020)
Melon (Cucumis melo L.) is a fruit much appreciated for its qualities and its production has been growing and gaining space in the national and international market. Noble melons are more susceptible to stresses caused by biotic and abiotic factors, however, silicon can alleviate these effects and can also increase the productivity and quality of the fruits produced. Silicon (Si) is not considered a nutrient, however its beneficial effects justify its application in commercial crops, and may even reduce the use of pesticides for the phytosanitary control of crops. Thus, the objective was (a) to evaluate the effect of foliar application of silicon on agronomic characteristics and its post-harvest quality, of frog skin melon in the field and protected environment; (b) to evaluate the effect of Si application on the productive, qualitative and nutritional characteristics of melon lace. Two experiments were developed. Experiment I: It was carried out with the melon skin frog variety, at the Federal University of Goiás from August to October 2018. The design was in randomized blocks, in a 5x2 factorial scheme, with five Si concentrations: 0.0 (control without Si), 0.3; 0.6; 0.9, 1.2 g L-¹ of Si, two production environments (protected and open field) with 4 repetitions. Plant height, stem diameter, leaf area, relative chlorophyll index and determination of gas exchange rates in the plant, and titratable acidity (AT), soluble solids (SS), pH, SS / AT ratio in fruits were evaluated . Experiment II: It was conducted with the variety of lacy melon, in a greenhouse at the Federal University of Piauí, from May to August 2019. The design was in randomized blocks, each plot was represented by a plastic pots with 15 dm3 of soil. The treatments consisted of five Si concentrations: 0.0 (control without Si), 0.3; 0.6; 0.9, 1.2 g L-¹ of Si with 4 repetitions. The following were evaluated: plant height, stem diameter, leaf area, chlorophyll index, dry mass of the aerial part, fresh weight of the fruit, circumference and length of the fruit, soluble solids (SS), titratable acidity (AT), ratio (SS / AT), productivity and accumulation of N, P, K, Ca, Mg and Si in the aerial part of the leaves and pulp of the lacy melon. The protected environment provided better growth for the frog skin melon. The application of silicon via leaf did not directly interfere in the growth of the frog skin melon, but indirectly provided better development, showing a significant effect on physiological variables such as transpiration and photosynthesis. Application of foliar silicon provided greater accumulation of potassium and calcium in the fruit pulp, greater titratable acidity, soluble solids and ratio (SS / AT) in the lacy melon. The concentration of silicon, which contributed most to the physiological variables and qualities of the fruit, ranged from 0.45 to 0.8 g L-1.